Nonlinear process modeling of pH neutralization process in CSTR using,selective combination of multiple neural Networks. - Ahmad, Zainal Ariffin; Abd Shukor, Syamsul Rizal (Universiti Sains Malaysia, 2008)

(untitled)
pH control problem is very important in many chemical and biological systems and especially in waste treatment plants. The neutralization is very fast and occurs as a result of a simple reaction. However, from the control point of view it is very difficult problem to handle because of its high nonlinearity due to the varying gain and varying dynamics with respect to the operating point.